1980
DOI: 10.1002/app.1980.070250904
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric loss microwave degradation of polymers: Cellulose

Abstract: SynopsisThe pyrolysis of organic waste polymers to produce fuels and chemicals is of interest to augment petroleum-based processes. The wide variety of pyrolysis products of low yield and the uncertain role that heat transfer rate plays in determining these have been deterrents to utilization in the past. A possible approach to increased selectivity for products is to heat them rapidly and homogeneously with the aim of narrowing the product distribution. A very rapid means of homogeneous heat transfer througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…The microwaves might be firstly used to activate biomass (cellulose as the feedstock) to solid, liquid and gas products by Allan et al in 1970s [70]. The studies of the research group led by Fernandez and Pis are mainly concentrated on the high-temperature microwave pyrolysis (more than 400 o C) of biomass [72,74].…”
Section: Pyrolysis In Microwave Reactormentioning
confidence: 99%
“…The microwaves might be firstly used to activate biomass (cellulose as the feedstock) to solid, liquid and gas products by Allan et al in 1970s [70]. The studies of the research group led by Fernandez and Pis are mainly concentrated on the high-temperature microwave pyrolysis (more than 400 o C) of biomass [72,74].…”
Section: Pyrolysis In Microwave Reactormentioning
confidence: 99%
“…The higher heating rate, the shorter residence time, and the faster the volatiles arrive to the external cold regions which, in turn, reduces the activity of secondary reactions of vapourphase products. This results in high yields of liquid and reduced deposition of refractory condensable material on the char's internal surface (Allan et al, 1980). In the case of materials with significant moisture content, like most biomass feedstocks, MP offers a different paradigm in particle heating where the electromagnetic field penetrates the solid, and interacts directly with dipoles in the chemical structure.…”
Section: Role Of Microwave Heating On the Pyrolysis Conditionsmentioning
confidence: 99%
“…Allan et al reported on the formation of,6-anhydro-b-Dglucopyranoside (levoglucosan), an interesting chiral synthon, when pyrolysing cellulose samples in a domestic microwave oven at 130 Watt for 5 min (Fig. 16) [42]. Yields in levoglucosan were moderate (about 40%), together with charred residues and water, whilst cellulose conversion was nearly quantitative.…”
Section: Hydrolysis and Pretreatment Of Cellulosementioning
confidence: 98%